Immunomodulator Activity and Antirheumatoid Arthritis Extract of Ethyl Acetate Ginseng Bugis Talinum Paniculatum (jacq.) Gaertn) - Andi Emelda (Journal of Global Pharma Technology, 2020)
The Immunomodulator is one of the compounds that can improve immune system. Chemical compounds work through the immune system to prevent and treat disease. Rheumatoid arthritis is an autoimmune disease that is chronic-systemic inflammation. The purpose of this study was to determine the effects of imonomodulator and antirheumatoid arthritis of ethyl acetate extracts of ginseng bugis leaves (Talinum Paniculatum (Jacq.) Gaertn). This study was divided into 2 groups, namely the immunomodulatory testing using sheep red blood cells and CFA-induced antirhematoid. This study used wistar rats which divided into 6 groups for immunomodulatory activity and 5 groups for antirematoid arthritis. The dose of ethyl acetate extract used was 0.05 g/KgBW; 0.1 g/KgBW, and 0.15 g/KgBW. Statistical test results for immunomodulatory activity showed significantly different results between the extract group doses of 0.05 g/KgBW; 0.1 g/KgBW, and 0.15 g/KgBW (p <0.05) with a negative control group. Rheumatoid arthritis testing showed (p <0.05) to the foot volume and arthritis index. The results showed that ethyl acetate extract of ginseng bugis leaves have immunomodulatory and antirheumatoid arthritis activity.Keywords: Immunomodulator, Anti Rheumatoid arthritis, Ethyl acetate, Talinum Paniculatum (Jacq.) Gaertn.